Plant chitinase III Ziz m 1 stimulates multiple cytokines, most predominantly interleukin-13, from peripheral blood mononuclear cells of latex-fruit allergic patients - Lee, Mey-Fann; Lin, Shyh-Jye; Wang, Nancy M.; Wu, Hsin-Ju; Chen, Yi-Hsing (Annals of Allergy, Asthma & Immunology, 2012)
Indian jujube is a fruit abundantly cultivated in Taiwan. Its major allergen in latex-fruit syndrome is Ziz m 1 of the chitinase III family. The Ziz m 1 Pichia (rZiz m 1-P) has chitinase activity but not Ziz m 1 E. coli (rZiz m 1-E). This study examined whether plant chitinase III, using rZiz m 1-P and rZiz m 1-E, can stimulate allergic inflammation similar to that of mammalian chitinases. Five patients allergic to latex–Indian jujube and five nonallergic controls were evaluated. Their peripheral blood mononuclear cells (PBMC) were cultured with rZiz m 1-E or rZiz m 1-P and pulsed with phorbol 12-myristate 13-acetate. Eleven cytokines were measured by FlowCytomix human Th1/Th2 plex kit and interleukin (IL)-13 by sandwich enzyme-linked immunosorbent assay (ELISA). Interleukin-13 significantly increased in rZiz m 1-P stimulated PBMC of allergic subjects but was undetectable when stimulated with rZiz m 1-E. The stimulation index significantly increased in IL-13 (380.6 ± 77.33 vs 13.70 ± 6.92), IL-5 (6.70 ± 0.59 vs 0.70 ± 0.37), IL-1β (32.70 ± 0.83 vs 2.10 ± 1.29), and tumor necrosis factor beta (TNF-β) (17.10 ± 2.66 vs 1.50 ± 0.66) between allergic and nonallergic subjects after rZiz m 1-P stimulation. There was no difference in terms of IL-2, IFN-γ, IL-8, and TNF-α production. The biological function of chitinase activity is required for Ziz m 1 to induce a Th2-specific immune response. This is the first report on PBMC responses of latex-fruit syndrome subjects toward an active exogenous plant class III chitinase that can stimulate multiple cytokines, especially IL-13, from allergic subjects. This implies the role of cross-reactive food allergens in propagating allergic inflammation among allergic subjects.